2006
DOI: 10.1111/j.1447-0756.2006.00437.x
|View full text |Cite
|
Sign up to set email alerts
|

Precedence of the shift of body‐fat distribution over the change in body composition after menopause

Abstract: An initial event during the menopausal process is BMD loss, which is followed by body fat distribution shift, then LBM loss and reciprocal increase in body fat mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 23 publications
2
30
1
Order By: Relevance
“…Our findings on changes of body fat in perimenopausal women are consistent with several previous crosssectional 6,10,16,19 and cohort 22 studies, but not with some other studies. 7,13 Our longitudinal data revealed that after adjusting for the other predictors, age was not associated with change of LM, and was negatively associated with percentage changes of TFM and T-LFMR.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings on changes of body fat in perimenopausal women are consistent with several previous crosssectional 6,10,16,19 and cohort 22 studies, but not with some other studies. 7,13 Our longitudinal data revealed that after adjusting for the other predictors, age was not associated with change of LM, and was negatively associated with percentage changes of TFM and T-LFMR.…”
Section: Discussionsupporting
confidence: 91%
“…1,[13][14][15] Although some crosssectional studies have observed greater fat mass and less lean mass in postmenopausal women, [6][7][9][10]16 others have not. 14,[17][18] The findings have been inconsistent even after separating age from menopause.…”
Section: Introductionmentioning
confidence: 99%
“…A reciprocal relationship between bone mass and bone marrow adiposity has often been noted in rodents and humans (Akune et al, 2004;Pei and Tontonoz, 2004;Morita et al, 2006). A deficiency in PPARc, a key mediator of adipocyte differentiation, reduces marrow fat and enhances osteogenesis in mice (Akune et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Menopausal transition is associated with a body fat redistribution leading to preferential abdominal adipose tissue (AT) accumulation [1,2]. High visceral AT accumulation has been associated with a deteriorated metabolic profile such as high triglyceride (TG) and low high-density lipoprotein cholesterol (HDL-C) concentrations in postmenopausal women [3,4].…”
Section: Introductionmentioning
confidence: 99%